Bibbie atlantiche e non solo nella biblioteca della cattedrale di Messina in epoca normanna - Caldelli, Elisabetta (Scrineum, 2018)
Studying the old Cathedral Library of Messina, whose holdings are today preserved mostly in Madrid (BNE), we have focused on the presence of at least two “Atlantic” Bibles and some non-biblical manuscripts with a format similar to that of the Bibles. The production of these books can be located in Central Italy, perhaps in Rome, since they share features of this region. They transmit mostly biblical commentaries or patristic writings, such as those of Augustine and Gregory the Great. Why were these manuscripts included in the holdings of the Cathedral Library and when? Three hypotheses will be pursued. First, someone from the cathedral staff could have commissioned them, as was the case for the manuscripts of the diocese of Troia, commissioned by Bishop William. Second, the manuscripts could have been bought by the clerics of the cathedral for liturgical needs; third, the manuscripts could have been left as gifts by a donor (one or more clerics) who had arrived in Sicily with his own books. Why was this format chosen for these books? Two hypotheses will be explored. First, the intent to declare the intellectual and political dependency of at least one part of the diocese of Messina on papal power as opposed to other political forces. Or, second, the need to provide books for liturgical and ecclesiastical uses, drawing from the books available in the Norman kingdom or in other lands. In the latter case, the presence of manuscripts with this format might be explained as a preference for book production other than that of Southern Italy, because it seems Norman readers did not have a taste for Southern Italian books in the Beneventana script.